Physical mesomechanics of crystal structure refinement upon severe plastic deformation; Physical mesomechanics; Vol. 11, iss. 5-6, Sept.-Dec. - Panin V. E. Viktor Evgenyevich (2008, 2008)
A mechanism of crystal structure refinement in solids subjected to severe plastic deformation is proposed in the framework of a multiscale approach adopted in physical mesomechanics and nonequilibrium thermodynamics. The basis of the mechanism observed in nanostructuring of metallic materials is fragmentation of bent band structures comprising subbands of a base material and a defect one. As the crystal subbands are fragmented the subbands of the defect phase occupy the interfaces between the fragments. "Chessboard-like" distribution of normal and tangential tensile and compressive stresses at the interface between the base and defect material plays an important role in this process. A lower limit to initial crystal structure refinement for different severe plastic deformation techniques is examined